INTERAKSI ISLAM DAN BUDAYA LOKAL DALAM TRADISI SYUKURAN LAUT DI KUALA JELAI KALIMANTAN TENGAH - Alimaturraiyah Alimaturraiyah; Zaenuddin Hudi Prasojo (Universitas Muhammadiyah Tangerang, 2020)
Every society has a culture that comes in various forms. One form of culture that can be found in our lives is the local culture. The Kuala Jelai community has local wisdom, which is an appreciation of the sea with the concept of sea thanksgiving. Local wisdom of a community is beneficial for other communities because the value of local wisdom is undoubtedly something that has been tested by time and space. This article is intended to elaborate on the tradition of sea Thanksgiving in Kuala Jelai, especially on the side of its preservation. Among the essential reasons for the tradition of sea thanksgiving is the role of the sea, which significantly helps the life of fishers, so that the people of Kuala Jelai held a thanksgiving sea as gratitude to God who has provided sustenance and safety for the fishermen and the surrounding community. In the process of implementing the sea thanksgiving tradition, there are several values contained therein, namely social values, religious values, and educational values